ANALISIS PENGARUH STRUKTUR KEPEMILIKAN MANAJERIAL DAN MEKANISME GOOD CORPOTARE GOVERNANCE TERHADAP MANAJEMEN LABA (Studi Empiris pada Perusahaan Manufaktur yang terdaftar di Bursa Efek Indonesia Tahun 2008-2010) - Andi Syarifuddin (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2013)
The purpose of this research is to examine the influence of the structure of ownership managerial and good corporate governance mechanism about earnings management in manufacturing companies listed at Indonesian Stock Exchange during 2008 to 2010. The examined variables in this research are consisting of independent variables, dependent variable and control variable. The independents variables such as the structure of ownership managerial and corporate governance mechanisms were measure by three variabels composition of board of commisioner and composition of audit committee. While, the dependent variable is earnings management which is measured by discretionary accrual estimated by using Jones modified model.The population of this research is 14 samples from manufacturing companies listed at Indonesian Stock Exchange during 2008 to 2010. The sampling method used in this research is purposive sampling method. In addition, the data analysis method used is analysis regression and descriptive statistics. The results of this research show that structure of ownership managerial, and composition of audit committee have significant relationships with earnings management. Next, variable composition of board of commisioner have no significant relationship with earnings management.